GE_GERICHTE P/257/2020 vom 7. November 2022 - GE Cour de justice (2022)
CONSTATATION DES FAITS;INFRACTIONS CONTRE LE PATRIMOINE;INFRACTIONS CONTRE LA LIBERTÉ;BAIL À LOYER | CPP.393; CPP.310; CP.156; CP.181; CO.263